Implicit computation complexity in higher-order programming languages: A Survey in Memory of Martin Hofmann - Dal Lago, U. (Mathematical structures in computer science, 2022)
This paper is meant to be a survey about implicit characterizations of complexity classes by fragments of higher-order programming languages, with a special focus on type systems and subsystems of linear logic. Particular emphasis will be put on Martin Hofmann’s contributions to the subject, which very much helped in shaping the field.